Analisis Pertumbuhan Dan Hasil Tiga Varietas Tanaman Nilam (Pogostemon cablin Benth.) Akibat Pengaturan Jarak Tanam - Akbar Hidayutallah Zaini; Didik Hariyono; Onny Chrisna Pandu Pradana; Septiana Septiana; Akbar Saitama (Politeknik Negeri Lampung, 2023)
Patchouli (Pogostemon cablin Benth.) is one of the essential oil-producing plants which is Indonesia's leading export commodity so that it can contribute foreign exchange for the country. Patchouli production nationally is still fluctuating and the productivity of patchouli oil is still relatively low. Therefore, proper patchouli cultivation techniques are needed. Plant distance is an important factor in determining the quality and quantity of production. In addition, the use of superior varieties is also a technology that aims to increase the productivity, yield and quality of patchouli oil. This study aims to determine the interaction and analyze the growth and yield of three varieties of patchouli (Pogostemon cablin Benth.) at different plant distance. This research was conducted in October 2021 â€“ March 2022 at the Experimental Garden of Agrotechno Park, Universitas Brawijaya, Jatikerto Village, Kromengan, Malang, East Java. The tools and materials used in this study were tractors, ovens, LAM, scales, hoses, alphaboard, polybags, stationery, cameras, patchouli seeds of Sidikalang variety, Patchoulina 1 variety, Patchoulina 2 variety, planting media, rainfall data, manure, fertilizer. Urea, KCL fertilizer, SP36 fertilizer, raffia rope and water. The design used in this study was the Randomized Block Design which was arranged in a factorial manner consisting of 6 treatment combinations and 4 replications, namely: V1J1: Sidikalang variety + 75 cm x 40 cm plant distance; V1J2: Sidikalang variety + 60 cm x 50 cm plant distance; V2J1: Patchoulina 1 + plant distance 75 cm x 40 cm; V2J2: Patchoulina 1 variety + 60 cm x 50 cm plant distance; V3J1: Patchoulina 2 variety + 75 cm x 40 cm plant distance; V3J2: Patchoulina 2 variety + 60 cm x 50 cm plant distance. The results showed that the treatment of varieties and plant distance had a significant effect on the components of patchouli plant growth. While the yield component of patchouli shows the interaction between varieties and plant distance. The conclusion of this study is that there is an interaction between the treatment of varieties and plant distance on the increase in fresh weight, dry weight and productivity of patchouli. The Sidikalang variety with a plant distance of 60 Ã— 50 cm had the highest yield and oil quality compared to other treatments. The Sidikalang variety also had the highest growth compared to the Patchoulina 1 and Patchoulina 2 varieties. Likewise, the 60 cm x 50 cm plant distance treatment had the highest growth compared to the 75 cm x 40 cm plant distance.